2009
DOI: 10.1109/tip.2008.2007049
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Shape-From-Focus for Holographic Reconstructions With Regard to Focus Operators, Neighborhood-Size, and Height Value Interpolation

Abstract: This paper presents a shape-from-focus method, which is improved with regard to the mathematical operator used for contrast measurement, the selection of the neighborhood size, surface refinement through interpolation, and surface postprocessing. Three-dimensional models of living human faces are presented with such a high resolution that single hairs are visible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 22 publications
0
63
0
6
Order By: Relevance
“…In order to compute modified Laplacian of image, Thelen et al [32] proposed vertical variations of the image. …”
Section: Diagonal Laplacianmentioning
confidence: 99%
“…In order to compute modified Laplacian of image, Thelen et al [32] proposed vertical variations of the image. …”
Section: Diagonal Laplacianmentioning
confidence: 99%
“…This problem was solved by several ways: varying size of computational pixel windows [33,36], averaging multiple snapshots taken at each vertical position [26], or input data averaging [37]. However, these methods are able to decrease a noise but the noise cannot be zeroed.…”
Section: The Thirdmentioning
confidence: 99%
“…Thelen et al improved this feature by taking into account the intensity information from diagonal pixels [10]. It is defined by …”
Section: Laplacian Based Featuresmentioning
confidence: 99%
“…Pech et al [9] suggested to use variance of the Laplacian operator convoluted with an input image. Thelen et al [10] created a modification of Nayar's SML feature, additionally taking into account the intensity information from diagonal pixels. Due to the increased amount of points used for calculation, this improved feature showed more reliable results on noisy images.…”
Section: Introductionmentioning
confidence: 99%